OPTIMIZATION OF ISLAMIC EDUCATION MANAGEMENT IN WELCOMING THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM - Albustomi, Abu yazid; Wahid, Abd Hamid; Najiburrahman, Najiburrahman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the implementation of the Independent Learning Curriculum at Madrasah Aliyah Nurul Jadid with a focus on the integration of Islamic education and worldly knowledge. The methods used are in-depth interviews with the principal, teachers, and students, as well as observations of the implementation of the curriculum. The results of the study indicate that this curriculum provides flexibility that allows educators to adjust teaching methods according to student characteristics and developments, without ignoring Islamic principles. Curriculum development focuses on strengthening academic competence and student character, while maintaining the integration of Islamic values in each subject. For example, in learning Indonesian, students are not only taught writing skills, but also Islamic ethical and ethical values in communicating. The competency-based Independent Learning Curriculum provides space for students to explore their interests and talents, while developing a strong character. However, the main challenge faced is maintaining a balance between worldly and religious knowledge, especially in avoiding neglecting Islamic values amidst academic demands. Good coordination between management, teachers, and the school committee is essential to ensure the successful implementation of this curriculum. Overall, this curriculum shows that education that integrates worldly and religious knowledge can produce students who are intelligent, have noble character, and are ready to face global challenges with a strong moral and spiritual foundation.